The Impact of Motivation and Organizational Commitment on Employee Work Performance - Anugrah Rossytasari; Sugiharto, Sugiharto; Achmad Daengs GS; Enny Istanti; Diana Zuhro (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The era of globalization has profoundly influenced various aspects of human life, breaking down national boundaries and reshaping international relations through advancements in information and communication technology. In Indonesia, this has significantly impacted industries such as trade, manufacturing, and services. Organizations face intense competition, making employee commitment essential for achieving company goals. Harmonious interpersonal relationships among employees foster trust and togetherness, which are crucial for sustaining high organizational commitment. Without mutual trust and group cohesion, employee commitment diminishes, reducing overall work performance. Clear and jointly established organizational goals provide guidance on responsibilities, workloads, and performance targets while serving as motivational challenges to enhance employee productivity. This study employs multiple linear regression analysis to examine the relationship between motivation, organizational commitment, and employee work performance. The simultaneous F test indicates a significant influence of independent variables on the dependent variable, with a calculated F value of 28.9701 exceeding the F table value of 3.19. The coefficient of determination (R²) is 0.5418, showing that 54.18% of the variance in employee performance is explained by motivation (X1) and organizational commitment (X2), while the multiple correlation coefficient (R) of 0.7361 indicates a strong overall relationship. Partially, organizational commitment exerts the most dominant effect on work performance, with a calculated t value of 5.4485 exceeding the t table value of 2.0096. Factors contributing to this influence include alignment of job characteristics with employee expectations, opportunities for skill development, provision of alternative job options, and organizational support for knowledge enhancement, all of which collectively improve employee work performance.